Early chronotype with metabolic syndrome favours resting and exercise fat oxidation in relation to insulin‐stimulated non‐oxidative glucose disposal. Issue 11 (19th September 2022) - Malin, Steven K.; Remchak, Mary‐Margaret E.; Smith, Anthony J.; Ragland, Tristan J.; Heiston, Emily M.; Cheema, Udeyvir
Abstract : New Findings: What is the central question of this study? Chronotype reflects differences in circadian‐mediated metabolic and hormonal profiles. But, does resting and/or exercise fuel use differ in early versus late chronotype as it relates to insulin sensitivity? What are the main finding and its importance? Early chronotypes with metabolic syndrome utilized more fat during rest and exercise independent of aerobic fitness when compared with late chronotypes. Early chronotypes were also more physically active throughout the day. Greater fat use was related to non‐oxidative glucose disposal. These findings suggest that early chronotypes have differences in fuel selection that associate with type 2 diabetes risk. Abstract: Early chronotypes (ECs) are often insulin‐sensitive, in part, due to physical activity behaviour. It is unclear, however, if chronotypes differ in resting and/or exercise fuel oxidation in relation to insulin action. Using the Morningness–Eveningness Questionnaire (MEQ), adults with metabolic syndrome (ATP III criteria) were classified as EC (MEQ = 63.7 ± 0.9, n = 24 (19F), 54.2 ± 1.2 years) or late chronotype (LC; MEQ = 47.2 ± 1.4, n = 27 (23F), 55.3 ± 1.5 years). Carbohydrate (CHO) and fat oxidation (FOX, indirect calorimetry) were determined at rest, 55% and 85% V ̇ O 2 max V_O_2max, along with heart rate and rating of perceived exertion. Physical activity patterns (accelerometers), body composition (DXA) and insulin sensitivity (clamp, 40 mU/m 2 /min, 90 mg/dl) with an indirect calorimetry for non‐oxidative glucose disposal (NOGD) were also determined. While demographics were similar, ECs had higher V ̇ O 2 max V_O_2max ( P = 0.02), NOGD ( P < 0.001) and resting FOX ( P = 0.02) than LCs. Both groups increased CHO reliance during exercise at 55% and 85% V ̇ O 2 max V_O_2max (test effect, P < 0.01) from rest, although ECs used more fat (group effect, P < 0.01). ECs had lower sedentary behaviour and more physical activity during morning/midday (both, P < 0.05). FOX at 55% V ̇ O 2 max V_O_2max correlated with V ̇ O 2 max V_O_2max ( r = 0.425, P = 0.004) whereas FOX at 85% V ̇ O 2 max V_O_2max related to NOGD ( r = 0.392, P = 0.022). ECs with metabolic syndrome used more fat in relation to insulin‐stimulated NOGD.